Climate change adaptation in rural South Africa: Using stakeholder narratives to build system dynamics models in data-scarce environments. Issue 1 (3rd April 2021) - Carnohan, Shane A.; Clifford-Holmes, Jai K.; Retief, Hugo; McKnight, Ursula S.; Pollard, Sharon
ABSTRACT: The need for innovative systemic approaches for managing water resources that integrate natural and human dimensions is well established. Although systemic, participatory modelling has been shown to support stakeholder involvement and integrated analysis, the uptake within acrimonious, data-scarce contexts – especially in the developing world – is limited. This study details a process designed to address challenges facing the lower Olifants River Catchment in South Africa, including deteriorating water quality, data paucity and stakeholder conflict. Narratives and quantitative data were used to build a system dynamics (SD) model, ResiMod, within a participatory process. The paper demonstrates how narratives can inform, and be informed by, iterative model development whilst integrating scientific data. The approach facilitated an exploration of perceptions of causality, connections between stakeholder sectors, and mitigatory actions for responding to climate-change impacts on biodiversity. This offers a promising approach to support improved communication and learning in disputed, data-scarce contexts.